2022
DOI: 10.3390/jpm12010122
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of the 13-Year Risk of Incident Atrial Fibrillation in a Russian Population Cohort of Middle and Elderly Age

Abstract: Atrial fibrillation (AF) is the most common arrhythmia and a predictor of the complications of atherosclerotic cardiovascular diseases (ASCVDs), particularly thromboembolic events and the progression of heart failure. We analyzed the determinants of the 13-year risk of incident AF in a Russian population cohort of middle and elderly age. A random population sample (n = 9360, age 45–69 years) was examined at baseline in 2003–2005 and reexamined in 2006–2008 and 2015–2017 in Novosibirsk (the HAPIEE study). Incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Two publications [ 42 , 75 ] reported results from two separate studies each and one publication reported results from five separate studies [ 29 ], two of which were included in the main analysis (the other three were surpassed by more recent publications, but results of two of these duplicate studies were included in subgroup analyses by ethnicity). Twenty six studies (23 publications) [ 18 , 20 , 21 , 25 , 27 30 , 33 , 36 , 42 , 43 , 48 , 54 , 64 , 65 , 69 , 71 73 , 75 , 76 , 78 ] were from Europe, twenty studies (25 publications) [ 7 , 17 , 19 , 22 , 24 , 26 , 29 , 31 , 34 , 37 , 40 , 41 , 45 47 , 52 , 53 , 56 , 59 , 67 , 68 , 70 , 74 , 77 , 81 ] were from North America, nineteen studies (19 publications) [ 23 , 32 , 35 , 38 , 39 , 44 , 49 51 , 55 , 57 , 60 63 , 66 , 79 , 80 , 82 ] were from Asia, and three studies (3 publications) [ 8 , 9 , 58 ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two publications [ 42 , 75 ] reported results from two separate studies each and one publication reported results from five separate studies [ 29 ], two of which were included in the main analysis (the other three were surpassed by more recent publications, but results of two of these duplicate studies were included in subgroup analyses by ethnicity). Twenty six studies (23 publications) [ 18 , 20 , 21 , 25 , 27 30 , 33 , 36 , 42 , 43 , 48 , 54 , 64 , 65 , 69 , 71 73 , 75 , 76 , 78 ] were from Europe, twenty studies (25 publications) [ 7 , 17 , 19 , 22 , 24 , 26 , 29 , 31 , 34 , 37 , 40 , 41 , 45 47 , 52 , 53 , 56 , 59 , 67 , 68 , 70 , 74 , 77 , 81 ] were from North America, nineteen studies (19 publications) [ 23 , 32 , 35 , 38 , 39 , 44 , 49 51 , 55 , 57 , 60 63 , 66 , 79 , 80 , 82 ] were from Asia, and three studies (3 publications) [ 8 , 9 , 58 ...…”
Section: Resultsmentioning
confidence: 99%
“…Although elevated blood pressure is an established risk factor for several cardiovascular diseases, data regarding blood pressure and risk of atrial fibrillation have to our knowledge not been summarized in a meta-analysis. A large number of cohort studies have investigated the association between hypertension and the risk of atrial fibrillation [ 7 9 , 17 65 ], and most of these found an increased risk [ 7 , 8 , 17 22 , 24 31 , 33 , 34 , 36 49 , 51 62 , 64 , 65 ], with few studies reporting no association [ 9 , 23 , 32 , 35 , 50 , 63 ], however, the strength of the association has differed considerably between studies with reported relative risks reported ranging from 0.93 to 2.85 [ 7 9 , 17 – 59 ]. In addition, several studies have investigated the association between systolic [ 8 , 18 , 20 , 29 , 33 , 34 , 39 , 41 , 42 , 44 , 46 , 51 , 55 , 63 , 65 80 ] or diastolic [ 8 , 29 , 33 , 39 , 41 , 44 , 46 , 51 , 55 , 67 70 , 72 74 , 79 , 81 ] blood pressure and risk of atrial fibrillation with most studies reporting increased risk for increasing systolic blood pressure [ 18 , 20 ...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The easily calculated immunological ratios of blood cells and Lp(a) concentrations can be considered simple predictors of future cardiovascular events. Shapkina et al [6] investigated the determinants of the 13-year risk of incident atrial fibrillation (AF) in a Russian population cohort of middle and elderly age. A random population sample (n = 9360, age 45-69 years) was examined at baseline in 2003-2005 and reexamined in 2006-2008 and 2015-2017 in Novosibirsk (the HAPIEE study).…”
mentioning
confidence: 99%
“…Shapkina et al [ 6 ] investigated the determinants of the 13-year risk of incident atrial fibrillation (AF) in a Russian population cohort of middle and elderly age. A random population sample ( n = 9360, age 45–69 years) was examined at baseline in 2003–2005 and reexamined in 2006–2008 and 2015–2017 in Novosibirsk (the HAPIEE study).…”
mentioning
confidence: 99%